Culture and Classroom Reform: The case of the District Primary Education Project, India - Clarke, Prema (Comparative Education, 2003)
Reform in teaching and learning forms one of the basic dimensions of educational reform. This study explores the impact of the reform process on teacher thinking and classroom practice in the multi-donor supported District Primary Education Project in Karnataka, India. Using both qualitative and quantitative methodologies, a variety of aspects dealing with teaching and learning are examined in order to understand the extent to which changes are taking place in the classroom. The study analyses the impact of four cultural constructs, which frame teaching and learning in India: holism as a shared worldview that encourages openness to regulation; the hierarchical structure as a regulative social framework; knowledge as discovered and attested collectively; and the ‘sense of duty’ that deﬁnes the role of the teacher (and student). The conclusion of the study is that while there are observable changes in the classroom in the use of instructional aids and activities during instruction, the essential characteristics of traditional practice, namely rote and repetition has not changed. Both teachers’ openness and resistance to reform are portrayed as embedded in the cultural construction of teaching and learning.

Factors Affecting Technology Uses in Schools: An Ecological Perspective - Zhao, Yong; Frank, Kenneth A. (American Educational Research Journal, 2003)
Why is technology not used more in schools? Many researchers have tried to solve this persistent puzzle. The authors of this article report on their study of technology uses in 19 schools. They suggest an ecological metaphor, using the example of the introduction of the zebra mussel into the Great Lakes, to integrate and organize sets of factors that affect implementation of computer uses. Their findings suggest that an ecological perspective can provide a powerful analytical framework for understanding technology uses in schools. That perspective points out new directions for research and has significant policy and practical implications for implementing innovations in schools.
Keywords: computers in schools; diffusion of innovation; educational technology; school ecology; teacher development